2023
DOI: 10.1128/aac.00900-22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pharmacokinetics of the GalNAc-Conjugated Antisense Oligonucleotide GSK3389404 in Participants with Chronic Hepatitis B Infection across the Asia-Pacific Region

Abstract: GSK3389404, an N-acetyl galactosamine-conjugated antisense oligonucleotide (ASO), was in clinical development for chronic hepatitis B (CHB) treatment. Few studies have examined ASOs in Asian participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…By contrast, 46.7% (7/15) of the clinical trials targeted the liver, and among the total 15, 20% of liver studies (3/15) were designated Randomized Control Trials (RCT), as compared to only one RCT study (6.7%) among all other organ systems. Among the RCT studies targeting the liver, GalNAc (N-Acetyl galactosamine) ASO conjugation was used in patients with chronic hepatitis B [ 11 ]. This modification involves attaching GalNAc molecules to the oligonucleotide, typically via a linker, which then facilitates specific binding to cell surface receptors known as asialoglycoprotein receptors (ASGPRs) primarily located on hepatocytes in the liver [ 122 ].…”
Section: Asos In Recent Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, 46.7% (7/15) of the clinical trials targeted the liver, and among the total 15, 20% of liver studies (3/15) were designated Randomized Control Trials (RCT), as compared to only one RCT study (6.7%) among all other organ systems. Among the RCT studies targeting the liver, GalNAc (N-Acetyl galactosamine) ASO conjugation was used in patients with chronic hepatitis B [ 11 ]. This modification involves attaching GalNAc molecules to the oligonucleotide, typically via a linker, which then facilitates specific binding to cell surface receptors known as asialoglycoprotein receptors (ASGPRs) primarily located on hepatocytes in the liver [ 122 ].…”
Section: Asos In Recent Clinical Studiesmentioning
confidence: 99%
“…In one mouse study, the targeted delivery of ASOs to hepatocytes using Gal-Nac structures improved the potency of targeting human apolipoprotein C-III and human transthyretin (TTR) 10-fold in mice [ 123 ]. The authors showed that plasma pharmacokinetics, their primary endpoint analysis, was not significantly altered in their Asia-Pacific population after using GSK3389404, a GalNac-conjugated ASO [ 11 ]. Two additional clinical trials were undertaken utilizing GalNAc3-conjugated 2′-O-methoxyethyl (2′MOE) ASOs in hepatic applications, demonstrating the well-tolerated nature of ASOs with no discernible class effect observed across all doses administered when compared to placebo [ 16 , 17 ].…”
Section: Asos In Recent Clinical Studiesmentioning
confidence: 99%